KERJASAMA KOMITE DAN SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA NEGERI 1 BATU AMPAR - F22210054, ISNAINI; ,, Aunurrahman; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: Cooperation is the joint effort of individuals and groups to achieve common goals. The cooperation Committee at the school because responsibilities helps schools achieve a quality. The research of this thesis aims to obtain infor-mation about: (1) How cooperation committees provide support learning in SMA Negeri 1 Batu Ampar? (2) supporting Factor and a barrier to cooperation between the Committee and the school? (3) The Committee's efforts to increase support to schools to enhance the implementation of the education quality?. This research uses descriptive method, intended to describe the symptoms, the actual event or occurrence as it is. The collection of data sources is performed with three kinds of methods of interviewing, observation, and documentation. Based on the results of the research done indicates that: (1) the forms of support Committee to the lear-ning activity is still low, focused on the development of the means of Government funds, (2) factors that strengthened cooperation between committees, namely in the form of reward factors that inhibit Cooperation Committee is the Committee on resources, recruitment, systems and implementation of the institutional Management Committee has not yet understood. (3) The school Committee's efforts to improve the support material and non material not optimal. Keywords: Cooperation, School Committee, Quality of Learning Abstrak: Kerjasama adalah usaha bersama individu dan kelompok untuk menca-pai tujuan bersama. Kerjasama komite di sekolah karena komite bertanggung ja-wab membantu sekolah untuk meningkatkan kualitas belajar. Penelitian tesis ini bertujuan untuk mendapat informasi mengenai: (1) Bagaimana kerjasama komite memberikan dukungan belajar di SMA Negeri 1 Batu Ampar? (2) Faktor pen-dukung dan penghambat kerjasama antara komite dan sekolah? (3) Upaya komite meningkatkan dukungan kepada sekolah melaksanakan proses belajar yang ber-mutu?. Penelitian ini menggunakan metode deskriptif, bermaksud mendeskripsi-kan suatu gejala, atau kejadian aktual sebagaimana adanya. Pengumpulan sumber data dilakukan dengan tiga jenis metode yaitu wawancara, observasi, dan doku-mentasi. Berdasarkan hasil penelitian yang dilakukan menunjukkan bahwa: (1) Bentuk dukungan komite terhadap kegiatan belajar masih rendah, tepusat pada pembangunan sarana dari dana pemerintah, (2) Faktor yang menguatkan kerja-sama komite yaitu imbalan dalam bentuk reward, Faktor yang menghambat kerja-sama komite adalah sumber daya komite, sistem rekrutment, dan implementasi kelembagaan yang belum difahami pengurus komite. (3) Upaya komite sekolah untuk meningkatkan dukungan materi dan non materi belum optimal. Kata Kunci : Kerjasama, Komite Sekolah, Mutu Belajar